The Development of E-Puzzle Learning Media on the Bhinneka Tunggal Ika Topic in Shaping the Profile of Pancasila Students in Grade X of MAN 1 Banyumas - Apriana Nurlaeli; Wildan Nurul Fajar; Elly Hasan Sadeli (UM Purwokerto Press, 2023)
This study aims to develop e-puzzle learning media for the